The Classical Tale from the Markandeya Purana (Ritudwaj and Madalasha) - Rana, Poonam RL (Nepalese Culture, 2024)
This paper sheds light on the intriguing ancient love story of Ritudwaj and Maladsha that is recounted in the Markandeya Purana, this paper investigates the classical account of the Purana. The Eastern world today is more familiar with Western classical love stories like Romeo and Juliet, Pride and Prejudice, Sense and Sensibility, Wuthering Heights, and Gone with the Wind, But Eastern readers have forgotten their classical legends. Ritudwaj and Madalasha's profound love is depicted in this undersea fantasy tale that delves into the classic love tale. This Pauranic tale is lovelier than Snow White or Cinderella. The researcher wishes to draw attention to the fact that our Puranas and other religious texts contain such beautiful love stories lost within the pages of such texts. This research aims to a) Highlight the ancient classical tale from Markandeya Purana. b) To open a venue for further research on such tales. The methodology used is exploratory based on the qualitative approach. This research is based on content study.